Physiological activity of Aloe vera in pacu (Piaractus mesopotamicus) inoculated with Aeromonas hydrophila - de Assis, Rudney Weiber Silva [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Springer Nature, 2020)
Aloe vera is a traditional medicinal plant; however, its use in fish is fairly recent. We evaluated the effects of dietary A. vera on stress, innate immunity, and energy metabolism in pacu inoculated with Aeromonas hydrophila. For 7 days, 192 fish were fed with diets supplemented with 0% (control), 0.5%, 1.0%, and 2.0% of the plant extract and then inoculated with bacteria and sampled 3, 6, and 24 h later. All concentrations of A. vera reduced basal levels of cortisol, and 1.0% reduced cortisol levels more intensely 3 h after inoculation. A. vera increased the basal respiratory activity of leukocytes/RAL (0.5 and 1.0%), increased the serum levels of lysozyme (1.0 and 2.0%) 6 h after inoculation, and increased the activity of the complement system after 3 h. Spleen somatic index/SSI increased with 1.0 and 2.0% A. vera. A. vera also promoted metabolic effects. It increased basal levels of lipids in the liver and muscle, as well as hepatosomatic index (1.0%) and, 3 h after inoculation, prevented the reduction of serum triglyceride (1.0%) and reduced the mesenteric fat (1.0%). Bacterial inoculation increased RAL from 3 to 24 h and lysozyme levels at 24 h, increased serum cholesterol at 24 h, and decreased serum triglyceride from 3 to 24 h, regardless of A. vera. We concluded that A. vera offered for only 7 days had stress-reducing effects, stimulated innate immunity, protected triglyceride levels in blood, lipid depots in the liver and muscle, and directed the energy mobilization to visceral depots.
Keywords: Fish farming; Herbal extracts; Innate immunity; Metabolism; Stress